JURIDICAL STUDY OF THE PROVISION OF PAYMENT OF WAGES BELOW THE MINIMUM WAGE BY EMPLOYERS TO WORKERS - Soedjarwo, Rieski Soerya; Karim, Dr Karim; Sugiharto, Dr. Sugiharto (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
Minimum wage regulation plays a central role in protecting workers' welfare and ensuring fair labor practices. In Indonesia, the enactment of Law Number 6 of 2023 reinforces this commitment by explicitly prohibiting employers from paying wages below the stipulated minimum and introducing criminal sanctions for violations. Despite these clear statutory mandates, sub-minimum wage payments persist in various sectors, raising critical concerns about the effectiveness of legal enforcement. This study applies a normative juridical method, examining the legal provisions governing minimum wage protections alongside the practical realities of labor law enforcement. The analysis reveals a systemic gap between the normative expectations of labor law and actual compliance in the field. Employers often rationalize non-compliance by citing financial pressures, while workers, due to economic vulnerability, frequently accept wages below the minimum standard. Enforcement agencies face significant limitations, resulting in rare prosecutions despite the existence of criminal sanctions. The findings highlight a discrepancy between the law’s protective intent and its practical implementation, reflecting broader challenges in Indonesia’s labor governance. The persistent failure to enforce minimum wage provisions not only undermines workers’ rights but also erodes trust in the legal system. This study underscores the need for critical reflection on the alignment between legal norms and labor market realities, emphasizing the importance of ensuring that statutory wage protections are not merely declarative but effectively upheld.